Agronomic responses of chili peppers to doses of nitrogen - Silva, Ricardo Barros; Barbosa, Wemerson Saulo da Silva; Santos, Wellington Manoel dos; Albuquerque Neto, João Cardoso de; Santos Neto, Antônio Lucrécio dos; Souza, Ademária Aparecida de; Martins, Gleica Maria Correia; Oliveira, José Dailson Silva de (Revista de Ciências Agroveterinárias, 2021)
Chili peppers hold great economic and social importance for producers due to growing demand from agribusinesses that make sauces with them. Nevertheless, studies on the nutritional management of chili peppers are scarce. Thus, fertilization of the crop is mainly empirical. This study was conducted to verify the influence that doses of nitrogen have on the yield of chili peppers. The experiment was conducted between August 2016 and May 2017 in the experimental area of the ​Arapiraca Campus of the Federal University of Alagoas in Arapiraca, Alagoas. A randomized block design with four replications was employed for six doses of nitrogen (0, 100, 200, 300, 400, and 500 kg ha-1 N). Nitrogen was applied in increments 108, 142, 172, and 202 days after planting (DAP); urea was the source of N. Harvesting began 90 DAP and on a weekly basis. The following variables were observed: plant height (m), canopy diameter (cm), SPAD index, number of fruits, and yield (t ha-1). The doses did not affect plant height and canopy diameter. The highest SPAD index (53.11), the greatest total fruit production by the end of the harvest period (2,773 fruits per plant-1), and the greatest yield (26.25 t ha-1) were verified with 500 kg ha-1 of N.